(untitled) (The Research of Medical Science Review, 2025)
Background: Every year, 120 million units of blood are donated globally. Individuals who donate blood are surely healthy individual. However, there may be a significant chance that receivers of improperly screened blood will contract blood-borne diseases. Objective: The study was aimed to evaluate the frequency of blood borne diseases among blood donors in district Swat. Methodology: This cross-sectional study was conducted by the department of microbiology, Government Degree College Madyan Swat. The study duration was six months from August 2023 to January 2024. The frequency of Syphilis, Malaria, HIV, HBV, and HCV in samples of blood donors was determined by using immune- chromatographic technique. All the data was entered and analyzed by using excel sheet. Results: This study includes 400 participants based on the inclusion criteria, where 100 (25%) were female and 300 (75%) were male. The age ranged was from 20 to 60 years. Over all the donors tested positive for HBV were 60 (15%), those who were positive for HCV were 120 (30%). Furthermore donors positive for HIV were 7 (1.75%). Moreover the donors positive for malaria were 70 (17.5%). And donors positive for syphilis were 30 (7.5%). Nearly the most affected age group was > 26 and < 50 years. Conclusion: The current study's findings regarding the prevalence of TTIs (Transfusion Transmitted Infections) among blood donors indicate that there is still significant threat to blood safety in Pakistan. Majority of donors were male (75%). The most common TTI infection was HCV (30%), followed by Malaria (17.5%) and HBV (15%). HIV (1.75%) and Syphilis (7.5%) was less prevalent.